14x+5=3(-x+3)-11

Simple and best practice solution for 14x+5=3(-x+3)-11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 14x+5=3(-x+3)-11 equation:


Simplifying
14x + 5 = 3(-1x + 3) + -11

Reorder the terms:
5 + 14x = 3(-1x + 3) + -11

Reorder the terms:
5 + 14x = 3(3 + -1x) + -11
5 + 14x = (3 * 3 + -1x * 3) + -11
5 + 14x = (9 + -3x) + -11

Reorder the terms:
5 + 14x = 9 + -11 + -3x

Combine like terms: 9 + -11 = -2
5 + 14x = -2 + -3x

Solving
5 + 14x = -2 + -3x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '3x' to each side of the equation.
5 + 14x + 3x = -2 + -3x + 3x

Combine like terms: 14x + 3x = 17x
5 + 17x = -2 + -3x + 3x

Combine like terms: -3x + 3x = 0
5 + 17x = -2 + 0
5 + 17x = -2

Add '-5' to each side of the equation.
5 + -5 + 17x = -2 + -5

Combine like terms: 5 + -5 = 0
0 + 17x = -2 + -5
17x = -2 + -5

Combine like terms: -2 + -5 = -7
17x = -7

Divide each side by '17'.
x = -0.4117647059

Simplifying
x = -0.4117647059

See similar equations:

| 42t^2-100t+50=0 | | -5(2x+5)=-25 | | 26-8x=3[2-4(x-7)] | | -10(s+3)=-62 | | -4=-8+4x | | 2y-8x=-2 | | 3(3x+7)=66 | | 5(2x+8)=120 | | 1.5d+3.25=1+22.5 | | 144/((72/4)/6) | | -13+3x=52+24x | | 2a(a-2)x=a-2 | | 313=-16t^2+153t+3 | | -5x-6=-42 | | x-3=46-6x | | 6x-4=-58 | | p(x)=6x^4-18x^3+6x^2-30x+36 | | Q=1/2P-4 | | 25+30x=295 | | D(x)=x^7+2*x^5+5*x | | 7x-5=-37+3x | | 3(4+4)= | | -58=x-7x+8 | | 3(4*3)= | | 3x^3-5x=2x^2+6 | | y^2-3y-44=0 | | 10n^2+11n+3=0 | | 3/4(5a-3=3/8 | | 3x-5=13+9x | | 6x^2-26x+8=y | | y=-1.5x+21 | | (z+9)(z-8)= |

Equations solver categories